DIVERSITY OF BEGONIA (BEGONIACEAE) IN BORNEO – HOW MANY SPECIES ARE THERE? - Julia Sang; Ruth Kiew (Reinwardtia, 2014)
A total of 126 species are currently named and described from Borneo (Brunei - 16 species, Kalimantan – 5 species, Sabah – 41 species and Sarawak – 72 species). However, based on our survey of the begonia collection in the Sarawak Herbarium, the un-named taxa (about 110 species) significantly outnumber the 72-named species. The situation is probably the same for Sabah, so with many more new species than the 41 named ones at a conservative estimate the Sabah begonia flora can be expected to exceed 100 species. For Kalimantan (5 named species), the total number of un-named species is likely to be even higher considering that Kalimantan occupies a larger land area, its begonia-rich mountains and limestone areas are hardly collected, and the begonia flora has hardly been studied at all. We can therefore expect the begonia flora of Borneo to exceed 600 species. In view of the high level of narrow endemism (80% of species are known from a single locality), expeditions to unexplored areas are necessary to document, in particular, areas that are experiencing irreversible land-use change. Alpha-taxonomy on a large scale is needed to tackle the backlog of literally hundreds of new undescribed species.